Maturity and spawning habits of Nemipterus japonicus (Bloch) off Visakhapatnam* - Rao, D Manikyala; Rao, K Srinivasa (Indian Journal of Fisheries, 2011)
The Japanese threadfin bream, Nemipterusjaponicus (Bloch) forms an important fishery(approx. 13%) among the demersalcatches landing at Visakhapatnam (Rao 1981).Earlier studies on N. japonicus include itsbiology (Kuthalingam 1965, Krishnamoorthi1971, Eggleston 1972, Murty 1984) andmaturity stages and fecundity (Dan 1977).Various aspects of maturity and spawningof this species were studied and are presentedhere.